Frequency of Common Hematological Diseases in Paediatric Patients Presenting with Clinical Features Indicative of Bone Marrow Examination - Sumira Abbas, Saba Khan, Mian Mufarih Shah, Sidra Basir, Shah Taj Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Haematological disorders are quite common in children. Bone marrow examination is a very important investigation for the diagnosis of many haematological and non haematological diseases. Objective: To determine the frequency of common hematological diseases in paediatric patients presenting with clinical features underling on biopsy. Material and Methods: This is a descriptive cross sectional study carried out at Hematology Department Hayatabad Medical Complex Peshawar from 19th Feb to 19th Aug 2018. A thorough relevant history was collected, and a clinical examination was performed. All haematological parameters were documented. Blood counts were carried out using an automated haematology analyzer. May – Grunwald Geimsa and Sudan Black B were used to stain peripheral blood and bone marrow smears, while haematoxylin and eosin was used to stain trephine biopsies. Exclusion criteria were used to compensate for confounding variables and bias. Results: A total of 290 patients were enrolled in this study. The range of age was between 2 months -15 years, with an average age of 8 years. Among 290 patients 211 (72.75%) male and 79 (27.24%) were female. 154 (53.10%) patients were in 2-8 years age group whereas 136 (46.89%) patients in 9-15 years age group. As per common hematological diseases, 72 (24.82%) patients were having megaloblatic anemia, 42 (14.48%) patients were having aplastic anemia, and 74 (25.51%) patients were having leukemia. Stratification of common hematological diseases with respect to age, gender and duration of disease are recorded. Conclusions: Leukemia is the commonest haematological disorder followed by megaloblastic anemia and aplastic anemia.